Interpretative Phenomenological Analysis of Self-Acceptance in Adolescent Girls with Stepmothers - Athalia Adzani Widyadhana (Cita konsultindo, 2025)
This study aims to analyze the phenomenon of self-acceptance in adolescent girls who have stepmothers, using an interpretive phenomenological approach. The main focus of this study is to explore the subjective experiences of adolescent girls in building self-acceptance in the context of their relationships with their stepmothers. The data collection technique used interviews with five research subjects. The data analysis technique in this study used the Interpretative Phenomenological Analysis (IPA) approach with the help of the Nvivo Version 12 program. The results of the study indicate that self-acceptance in adolescent girls with stepmothers is influenced by various factors, including the dynamics of interpersonal relationships with stepmothers, the role of emotional support from the family, and the adolescent's personal experiences related to self-identity and feelings of being accepted in the family. This self- acceptance is influenced by how adolescent girls relate to their stepmothers, as well as how they accept changes in their family structure. Adolescent girls may feel threatened or unaccepted, especially if their relationship with their biological mother was previously very strong. The mismatch between the real self and the ideal self, especially if they feel they have to adjust to the expectations or standards of their stepmother, can affect their self-acceptance.